Newborn son hyperthyroid mother, you can receive exclusive breastfeeding ?. - Kusunoki, Lourdes (2015)
Because thyroid disease is more common in women, pregnancy complicated with thyrotoxicosis is not uncommon, reporting in the US. UU. an incidence of 0.2% (1.2). Meanwhile, in our, country fluctuates, depending on the series, 0.03% in the Loayza Hospital to 0.12% in the Dos de Mayo Hospital 3.4. The handling of this problem remains controversial. Once the surgery is advocated, ideally in the second quarter. This behavior has been neglected, being used more frequently antithyroid such as Tapazol, in our midst.